Sensitivity analysis of a fumigant movement and loss model for bulk stored grain to predict effects of environmental conditions and operational variables on fumigation efficacy. (September 2018) - Plumier, Benjamin M.; Maier, Dirk E.
Abstract: In order to improve fumigation effectiveness and address phosphine resistance concerns, fumigant concentrations and movement in a grain storage silo need to be understood. In a previous study a mathematically accurate fumigation model was developed that is capable of predicting fumigant concentration and movement throughout a grain storage silo by taking into account fumigant loss from leakage and sorption. This model was used to investigate the impact on a phosphine fumigation with changing operational variables and environmental conditions. These included modifying the initial values from the fumigation by ± 25% and 50% for leakage rates, air recirculation rates, air temperature, relative humidity, and wind speed. Reducing leakage rate to 50% and 75% of the original rate increased fumigant concentrations by 111% and 36% compared to −21% and −34% for 125% and 150% leakage rate changes, respectively. Likewise, by the end of the simulation, average phosphine concentrations changed by 118%, 41%, −28%, and −47% for the 50%, 75%, 125%, and 150% air recirculation rates, respectively. Results underline the importance of designing well sealed silos and the importance of monitoring fumigations during high wind speed weather events. Highlights: Fumigation sensitivity to common variables was investigated with a finite element model. Operational parameters such as air recirculation rates and leakage rates were investigated. Weather effects such as temperature, relative humidity, and wind speed were investigated. Results are compared for scale and effect of impact to on farm fumigators.